Maqashid Shari'ah in Digital Tourism: Harmonizing Technology and Local Wisdom in Marine Tourism in Lampung, Indonesia - Hayati, Mardhiyah; Heri, Mad; Susanto, Is; Nurmalia, Gustika (Universitas Islam Negeri Raden Intan Lampung, 2024)
Digital tourism and the use of local wisdom in marine tourism are integral parts of the tourism destination promotion strategy. By utilizing digital technology and local values, the promotion of marine tourism destinations can be carried out more effectively. The use of social media, tourism websites, and various travel applications is a means to expand the reach of information to potential tourists. Lampung has great tourism potential, especially in the marine tourism sector, but requires an integration between digital technology and local wisdom to maximize this potential. This research highlights the importance of harmonization between technological advances and the preservation of local culture in the context of Lampung tourism. The research method used is qualitative descriptive with an interdisciplinary approach of literature study. Thematic analysis and content analysis are used to ensure the validity of the data and draw conclusions. The results of the study show that through the analysis of digital tourism practices and local wisdom, this study emphasizes the importance of maintaining environmental and cultural sustainability in the development of Lampung tourism. The integration of Maqashid Shari'ah in digital tourism is expected to bring economic benefits, positive impacts to local communities, and environmental sustainability in the development of marine tourism in Lampung.